Explaining the digital transformation of mathematics learning through the flipped classroom: A prisma bibliometric review - Pradana, Pascalian Hadi; Afandi, Ahmad (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
This study aims to systematically examine publication trends, implementation methods, pedagogical approaches, impacts, target education levels, and the role of digital technology in the application of the flipped classroom model in mathematics learning. The method used is the Systematic Literature Review (SLR) based on PRISMA guidelines, with additional bibliometric analysis using VOSviewer to map the relationship and development of keywords in the literature published between 2023 and 2025. The analysis of 16 selected articles indicates a growing research trend, marked by a shift from conceptual investigations toward studies emphasizing impact and student learning experiences. The results show that digital transformation in mathematics learning is reflected through the integration of digital instructional videos, LMS platforms, and online learning resources that restructure learning from a teacher-centered approach to a technology-supported, student-centered model. The findings also indicate a shift in research focus from conceptual discussions toward practical implementation and learner outcomes. The flipped classroom is implemented through a combination of pre-class digital preparation and in-class interactive activities that promote autonomy, engagement, and 21st-century skills. Despite variations in context, many of the identified challenges, such as limited digital competence and low pre-class engagement, remain relevant to Indonesian students. Overall, the study successfully addresses its objectives and provides insights that can serve as a reference for developing contextual, technology-driven mathematics learning strategies.